Simultaneous Quantification Of Β-Amyrin And Stigmasterol In Putranjiva Roxburghii Wall. By High-Performance Thin-Layer Chromatography - MADHAVI BADOLE,; DR.VIDYA DIGHE,; GAAUREE CHAREGAONKAR, (International Journal of Pharma and Bio Sciences, 2011)
HPTLC method for simultaneous determination of β-amyrin and stigmasterol in Putranjiva roxburghii wall. has been developed and validated. The analytes were separated on silica gel 60F254 HPTLC plates with n - hexane: chloroform: methanol (3: 6.5:0.5 v/v/v) as mobile phase after chamber saturation for 10 min. The development distance was 80mm. The derivatization was done by using anisaldehyde – sulphuric acid reagent. Detection and quantification were performed by densitometry, with a tungsten lamp, at 580 nm. The response to β-amyrin and stigmasterol was linear in the concentration range 0.045 to 0.360 μg per band and 0.041 to 0.328 μg per band respectively. The validated method was used for quantitative analysis of β-amyrin and stigmasterol in Putranjiva roxburghii wall. and can be used for routine quality-control analysis of leaf powder of Putranjiva roxburghii wall.